Severe asthma assessment, management and the organisation of care in Australia and New Zealand: expert forum roundtable meetings. Issue 2 (25th February 2021) - Maltby, Steven; McDonald, Vanessa M.; Upham, John W.; Bowler, Simon D.; Chung, Li P.; Denton, Eve J.; Fingleton, James; Garrett, Jeffrey; Grainge, Christopher L.; Hew, Mark; James, Alan L.; Jenkins, Christine; et al.
Abstract: Severe asthma imposes a significant burden on individuals, families and the healthcare system. Treatment is complex, due to disease heterogeneity, comorbidities and complexity in care pathways. New approaches and treatments improve health outcomes for people with severe asthma. However, emerging multidimensional and targeted treatment strategies require a reorganisation of asthma care. Consensus is required on how reorganisation should occur and what areas require further research. The Centre of Excellence in Severe Asthma convened three forums between 2015 and 2018, hosting experts from Australia, New Zealand and the UK. The forums were complemented by a survey of clinicians involved in the management of people with severe asthma. We sought to: (i) identify areas of consensus among experts; (ii) define activities and resources required for the implementation of findings into practice; and (iii) identify specific priority areas for future research. Discussions identified areas of unmet need including assessment and diagnosis of severe asthma, models of care and treatment pathways, add‐on treatment approaches and patient perspectives. We recommend development of education and training activities, clinical resources and standards of care documents, increased stakeholder engagement and public awareness campaigns and improved access to infrastructure and funding. Further, we propose specific future research to inform clinical decision‐making and develop novel therapies. A concerted effort is required from all stakeholders (including patients, healthcare professionals and organisations and government) to integrate new evidence‐based practices into clinical care and to advance research to resolve questions relevant to improving outcomes for people with severe asthma.